Food laborers as stewards of island biocultural diversity: reclaiming local knowledge, food sovereignty, and decolonization - Marrero, Abrania; Nicoson, Christie; Mattei, Josiemer (Frontiers in Sustainable Food Systems, 2023)
Creating nutritious and ecologically regenerative food cultures depends on the local knowledge of food system laborers. Food producers in small island developing states center socioecological interdependence in their livelihoods and, as such, conserve biocultural diversity. Amid burgeoning health, economic, and climate crises brought on by colonialism, reclaiming food sovereignty requires a critical and embodied scientific approach, one that considers what traditional ecological knowledge is and who creates and sustains it. This study positions laborers as the primary sources of knowledge in island food systems; discusses declines in nutrition and agrobiodiversity as consequences of food labor loss; and proposes laborers’ stewardship as essential to regenerating self-determination. Using critical quasi-ethnographic methods, this report synthesized primary data from narrative interviews in Guam (Guåhan, n = 13) and Puerto Rico (Borikén, n = 30), two former colonies of Spain and current territories of the United States, as specific examples of place-based knowledge production, interwoven into critical discussion of broader literature in this space. Our findings show that local food laborers combine intergenerational, ecosystem-specific knowledge with robust human value systems, negotiating across competing economic, cultural, and ecological needs to sustain livelihoods and regenerate biodiversity. As well-connected nodes in family and community networks, laborers serve as the scaffolding on which compassionate and relational care can thrive. Trade policies and the market dominance of transnational food corporations have severely reduced local food production in favor of food import dependence in islands, aggravating labor shortages and augmenting food insecurity. Through waves of out-migration and cash remittance, social care relationships have become monetized, reinforcing mass-produced food consumption and dietary diversity loss as islanders, both at home and in the diaspora, transition to an industrialized diet. The loss of local labor similarly poses threats to agrobiodiversity, with export-oriented agribusiness simplifying landscapes to streamline extraction. This study demonstrates that to reclaim food systems in Guam, Puerto Rico, and similar island settings, laborers must be valued as stewards of cultural and agrobiodiversity and can be integral to efforts that preserve cultures, agroecosystems, and health.